The Use of Clinical Supervision by Argentine Psychotherapists and its Link with the Basic Clinical Competencies for the Practice of Psychotherapy (Revista de Psicología, 2025)
Supervision aims to improve professional performance and the quality of professional services offered to those who consult and would improve results in psychotherapeutic processes. Despite the importance of the supervision process, there are few local studies that describe its use; therefore, this work aims to understand the use of supervision by Argentine psychotherapists and the differences in performance in the supervision process. For this, an empirical methodology with a quantitative approach and a non-experimental, transversal, descriptive and correlational design was used in which 534 psychotherapists from Argentina participated. The Scale of Basic Clinical Competencies for Psychotherapists was used, which aims to evaluate the Basic Clinical Competencies for the practice of psychotherapy and the indicators associated with its development through three evaluation modalities: resolution of clinical cases, self-assessment and questionnaire. The use of supervision by psychotherapists is described, the differences found with the levels of competence evaluated using the Scale of Basic Clinical Competencies for Psychotherapists  and the results are compared with other studies with similar characteristics. The results obtained allow us to know local data that could be used to optimize the supervision device, detect problems and deficits in performance and have greater tools to generate the conditions for their remediation.
Keywords: Supervision; Psychotherapy; Argentine Psychotherapists; Clinical Competences